Barriers to entry: Challenges facing youth entrepreneurs as they establish their small and medium enterprises (SMEs) in Egypt - Zamzam, Roqaya (AUC Knowledge Fountain, 2017)
This study aims at exploring the challenges faced by emergent youth entrepreneurs as they enter the market in Egypt. The qualitative approach incorporates semi-structured interviews with youth entrepreneurs who own SMEs in different sectors. The concepts underlying the legal and non-legal institutions are used to help present the different hinders to SMEs and youth entrepreneurial development. The research has shown that the lack of financing options, the inconsistent legal changes, the administrative burdens, the poor physical infrastructure, the lack of specialization along with market dominance are the main obstacles facing youth and SMEs. The study contributes to the literature on entrepreneurship in Egypt and highlights entrepreneurship challenges in order to present potential solutions that could help promote an enabling environment for youth to efficiency and effectively contribute to the economy.